Dissipative performance of dielectric elastomers under various voltage waveforms. Issue 8 (21st January 2016) - Zhang, Junshi; Li, Bo; Chen, Hualing; Pei, Qibing
Abstract : Taking the viscoelasticity and leakage current into account, we developed an analytical model to investigate the dissipative performance of dielectric elastomers under various voltage waveforms. Abstract : The actuation performance of dielectric elastomers (DEs) is affected by dissipation. In the present article, an analytical model is developed to investigate the dissipative performance of DEs by considering viscoelasticity and leakage current. Various voltage waveforms, such as DC voltage, square voltage, stepwise DC voltage, ramp voltage, sawtooth voltage, and triangular voltage, were applied to explore the dissipative performance of DEs. The DEs with diverse moduli and viscoelasticity intensities were also analyzed by comparing the different dissipative performances. Numerical calculations were employed to evaluate the dissipative behavior of DEs. When the value of the applied voltage is maintained invariable, the stretch gradually creeps, and the total current from the battery and the leakage current approach each other eventually. When the applied voltage varies linearly, the stretch deforms dramatically, and then the total current from the battery is much larger than the leakage current.